Pharmacological effect of Allium sativum on coagulation, blood pressure, diabetic nephropathy, neurological disorders, spermatogenesis, antibacterial effects - Seyyed Abbas Hashemi; Sayeh Ghorbanoghli; Ali Asghar Manouchehri; Mahdi Babaei Hatkehlouei (AIMS Agriculture and Food, 2019)
For many years, the medicinal plants have been used all over the world for treating and preventing from some diseases. But the effects of some of them have been examined scientifically. The medicinal plants are useful treating methods in both traditional and modern systems. The allium species like garlic and onion are used as food, spices, flavor and local drugs. With the scientific name of Allium sativam, the garlic is from the Liliaceae family and it has attracted a special attention among the modern plants, because it has been spread and is available all over the world. The findings of this study indicate that the garlic consuming can increase infection of some of bacteria. Due to the antioxidant characteristics, the garlic is likely to reduce these hurts significantly through increasing the antioxidant capacity in the kidney. There are several reports on the anticoagulation characteristics of garlic. Also there are some warnings about the simultaneous consumption of the garlic with warfarin and nonsteroidal anti-inflammation drugs. And also, garlic has anti-hypertensive characteristics and its compounds have been investigated in treating infertility, according to the studies done, garlic and the old garlic’s extract have anti-stress, anti-aging, memory and learning improving and anti-Alzheimer characteristics. But more studies are needed to be done on the humans in this context.